EXPERT COUNCIL RESOLUTION ON THE DEFINITION OF TACTICS OF MANAGING PATIENTS WITH HYPOPHOSPHATASIA FOLLOWING THE MEETING OF NOVEMBER 21, 2015, MOSCOW - article Editorial (Педиатрическая фармакология)
EXPERT COUNCIL RESOLUTION ON THE DEFINITION OF TACTICS OF MANAGING PATIENTS WITH HYPOPHOSPHATASIA FOLLOWING THE MEETING OF NOVEMBER 21, 2015, MOSCOW